Reagan and Thatcher's special relationship : Latin America and Anglo-American relations - Treharne, Sally-Ann (Edinburgh studies in Anglo-American relations., 2015)
A unique insight into one of the most controversial political relationships in recent history. The Falklands War, the US invasion of Grenada, the Anglo-Guatemalan dispute over Belize and the US involvement in Nicaragua - in the 1980s, these crises threatened to overwhelm a renewal in US-UK relations. US President Ronald Reagan and UK Prime Minister Margaret Thatcher's efforts to normalise relations, during and after these crises, reveal a mutual desire to strengthen Anglo-American ties and safeguard individual foreign policy objectives. At the same time, they cultivated a close political and personal bond that lasted well beyond their terms in office. Sally-Ann Treharne vividly portrays the role of personal diplomacy in overcoming obstacles to Anglo-American relations emanating from the turbulent Latin American region in the final years of the Cold War. Drawing on recently declassified documents and elite interviews with key protagonists that reveal candid recollections, she highlights the pivotal moments in Reagan and Thatcher's shared history from a new vantage point. Key Features. Based on strong documentary analysis including new, revealing primary documents from both British and American archival sources Draws on recent interviews with former aides/advisers to the Prime Minister, members of the Thatcher government and a member of the FCO Interviewees include: Lord Geoffrey Howe, Lord Michael Heseltine, Lord Cecil Parkinson, Sir John Nott, Sir Bernard Ingham, Lord Charles Powell, Baroness Gloria Hooper, Sir Adrian Beamish, Lord Peter Carrington, Lord Neil Kinnock and Lord Timothy Bell